Il paesaggio nel governo del territorio (2018)
Can today’s landscape become a living construct again, moved and shaped by a plurality of actors working for its maintenance with shared modalities? This text investigates the landscape’s role and its structural features in the governance of the territory, starting from Tuscany’s experience with landscape planning: this polyphonic, rich and multifaceted reflection is aimed at promoting the birth of communication tools and agreements, which not only strengthen the decision-making system from the bottom (in order to overcome the acknowledged detachment between plans, policies and common sentiment), but also open the way to the renewal of the consolidated structures of representative democracy.